2015
DOI: 10.1186/s12951-015-0101-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Hepatitis E virus like particles can function as RNA nanocarriers

Abstract: BackgroundAssembled virus-like particles (VLPs) without genetic material, with structure similar to infectious virions, have been successfully used as vaccines. We earlier described in vitro assembly, characterisation and tissue specific receptor dependent Clathrin mediated entry of empty HEV VLPs, produced from Escherichia coli expressed HEV capsid protein (pORF2). Similar VLP’s have been described as a potential candidate vaccine (Hecolin) against HEV.FindingsWe have attempted to use such recombinant assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Recombinant VLPs have been used in immunological, structural and virus research including studying virus-host cell interactions (Charpilienne et al, 2002), as surrogates in environmental persistence and inactivation studies (Caballero et al, 2004) and as vehicles to deliver epitopes and genes (Panda et al, 2015; Pushko et al, 2013). Furthermore, VLPs have been often evaluated as safe and effective vaccines for many viruses including influenza (Kushnir et al, 2012; Pushko et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant VLPs have been used in immunological, structural and virus research including studying virus-host cell interactions (Charpilienne et al, 2002), as surrogates in environmental persistence and inactivation studies (Caballero et al, 2004) and as vehicles to deliver epitopes and genes (Panda et al, 2015; Pushko et al, 2013). Furthermore, VLPs have been often evaluated as safe and effective vaccines for many viruses including influenza (Kushnir et al, 2012; Pushko et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Gene delivery to liver-derived cells has already been explored using HBV- and HEV-like particles 33,34 . In those experiments, foreign molecules were displayed on the particle surface by recombinant expression vectors where the viral capsid protein and foreign genes were encoded.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that long DNA and RNA molecules may be incorporated into VLPs. For example, mRNA for the reporter protein, red fluorescent protein, was packaged into particles representing the hepatitis E capsids [50]. The plasmid containing the green fluorescent protein (GFP) gene was encapsidated into the VLPs assembled in vitro from the main capsid protein of the hamster polyoma virus [51].…”
Section: Natural Sources For Vlp Bioengineering and The Specificmentioning
confidence: 99%